Economic evaluation of small wind turbines and hybrid systems for residential use: The case of Romania - Predescu, Mihai (2016)
Renewable electricity generating systems are gaining ground in residential sector for the purpose of diminishing the electricity bills or to reaching some degree of energy independence. The decision to invest in small wind turbines or hybrid energy generation technologies should be based on an economic evaluation of money invested in such systems. LCOE calculation for local technologies of choice for residential energy generation is a very reliable figure for deciding whether the investment can bring financial satisfaction and for selecting which type of technology is the best suited for a specific location.